Literary Performance in the Act of Pendendang - Noni Sukmawati (IJCAS (International Journal of Creative and Arts Studies), 2016)
This study is aimed to find out the power of pendendang as the main actor in Sastra Pertunjukan (Literary Performance), an art performance which places literature – in this case pantun or verse as the spoken literature of Minangkabau – as the main medium. Pantun is delivered through berdendang or singing tradition which is accompanied by an instrument named saluang. Hence this performance is so called saluang dendang performance. The main strength of this performance is the selection of the pantun delivered by pendendang and his ability to build a contextual connection or to interact with the audience or the surroundings.Pendendang combines the pantun with the new pantun and creates new ones spontaneously and contextually in his live performance. Therefore, this art performance of Minangkabau is also a literary performance because of the main strength lies on the pantun that are delivered. Framed in the theoretical proposition of Pierre Felix Bourdieu, this study tries to recite the role and the pendendang’s strength to improvise in his efforts to create an interesting performance for the audience, through his selection of pantunthat is delivered spontaneously and his mastery, habitus and position in the performance.